Juan Moreira - Gutiérrez, Eduardo, 1851-1889. (Narrativa. (Linkgua Ediciones), 2019)
Eduardo Gutiérrez's novel Juan Moreira was very popular and adapted for the theater, cinema, and comics. His other works include El Chacho, Hormiga Negra, Santos Vega, Juan Cuello, and Croquis y Siluetas Militares.